2022
DOI: 10.1289/ehp9620
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Outdoor Particulate Matter Air Pollution and Risk of Gastrointestinal Cancers in Adults: A Systematic Review and Meta-Analysis of Epidemiologic Evidence

Abstract: Background: Outdoor air pollution is a known lung carcinogen, but research investigating the association between particulate matter (PM) and gastrointestinal (GI) cancers is limited. Objectives: We sought to review the epidemiologic literature on outdoor PM and GI cancers and to put the body of studies into context regarding potential for bias and overall strength of evidence. Methods: We conducted a systematic review and meta-analysis of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 66 publications
(161 reference statements)
1
44
2
Order By: Relevance
“…PM2.5 can be suspended in the air for an extensive time and, in addition, can contain or adsorb heavy metals, toxic gases, polycyclic aromatic hydrocarbons, bacterial viruses, and other harmful substances. Moreover, PM2.5 can enter the bronchi and alveoli before finally entering the blood, causing damage to multiple organs, especially those of the respiratory and cardiovascular systems [2][3][4][5]. The Global Environment Outlook 5 released by the United Nations Environment Program in 2012 highlighted that the fine particles in air pollution cause more than two million deaths globally every year and cause huge economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…PM2.5 can be suspended in the air for an extensive time and, in addition, can contain or adsorb heavy metals, toxic gases, polycyclic aromatic hydrocarbons, bacterial viruses, and other harmful substances. Moreover, PM2.5 can enter the bronchi and alveoli before finally entering the blood, causing damage to multiple organs, especially those of the respiratory and cardiovascular systems [2][3][4][5]. The Global Environment Outlook 5 released by the United Nations Environment Program in 2012 highlighted that the fine particles in air pollution cause more than two million deaths globally every year and cause huge economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…We included comprehensive analysis to re-calculate duplicated or shared data appeared in two or more analyses [ 19 , 20 ]. The exclusion criteria were as follows: (1) reviews, letters, and reports, (2) animal- or cell-related data, (3) studies without subdivision of the types of particulate matter, (4) studies without PM2.5 increment data, (5) data collection time less than one year, and (6) studies on acute liver disease but not chronic liver disease [ 19 , 20 , 21 , 22 ]. Based on the inclusion criteria, J.S.…”
Section: Methodsmentioning
confidence: 99%
“…Current meta-analyses of PM2.5 and chronic diseases primarily focus on the morbidity and mortality of respiratory system diseases, cancer, cardiovascular and cerebrovascular disease [ 14 , 15 , 16 , 17 , 18 ]. In the literature, there are four meta-analyses [ 19 , 20 , 21 , 22 ] which have examined the association between PM2.5 and the incidence or mortality of liver cancer in nine epidemiological studies. In the above meta-analysis studies, only Wu et al reported that PM2.5 was significantly associated with the incidence and mortality of liver cancer (hazard ratio (HR) = 1.28, 95% confidence interval (CI): 1.15–1.41; HR = 1.21, 95% CI: 1.13–1.29, respectively) [ 22 ], while others only examined the mortality of liver cancer [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once in the gastrointestinal tract, air pollutants may interact with the intestinal epithelium, promoting the production of reactive oxygen species and pro-inflammatory oxidative lipids and contributing to the development of intestinal diseases [ 16 , 17 ]. In support of this hypothesis, recent studies have associated air pollution with intestinal diseases [ 13 ], including colorectal cancer [ 18 ] and inflammatory bowel diseases [ 19 ].…”
Section: Introductionmentioning
confidence: 99%